Policy advocacy campaign in the Philippines: Omnibus revisions of the Ecological Solid Management Act 2000 Republic Act no. 9003 (PACPORRA 9003) - Era, Marlon de Luna (Animo Repository, 2010)
Ecological Solid Waste Management Act 2000